EFISIENSI TEKNIS USAHATANI KEDELAI PADA LAHAN TADAH HUJAN DAN LAHAN KERING DI KABUPATEN PIDIE JAYA, ACEH - Muhammad Ismail; Anna Fariyanti; Amzul Rifin (Magister Science of Agribusiness, Department of Agribusiness, FEM-IPB University, 2017)
National soybean productivity was reach 1,45 tons per hectare, while the potential yield reach 2,0-3,0 tons per hectare. The aim of this study was to analyze the factors affecting technical efficiency, and sources of technical inefficiency of soybean farming. This study used primary data that were obtained from 100 farmers purposively, those data were analyzed by production function analysis that stochastic frontier to analyzed the factors that influence the production of technical efficiency of soybean farming. The results showed that the variable land, solid fertilizer, liquid fertilizer, pesticide solid, liquid pesticides, and labor have a positive impact, while the variable seed has a negative impact on technical efficiency of soybean farming. The source of technical inefficiency such as the age of the farmer, and experience farming soybean have negative and significant impact on technical inefficiency of soybean farming. Otherwise, the formal education, old farming, the number of dependents, and the dummy variable (following the extension and land type) have a positive impact but not significant to technical inefficiency of soybean farming in Pidie Jaya, Aceh Province.